Implementation of the Tartila Method in Improving Ability Read the Koran at TPQ al-Mubarok Sukodermo Purwosari Pasuruan - Hasanah, Uswatun; Muhammada, Muhammada; Ma’ruf, Ahmad (Sean Institute, 2023)
This tartila method is a method that reads the Qur'an with a direct focus on the practice of reading. The tartila Method Guide consists of 4 parts, the first level starts from the simple level, step by step to the perfect level. In the process of implementing al-Qur’an learning, TPQ al-Mubarok decided to use the tartila method based on the fact that this method is compatible with the development and abilities of children and the spirit of Ahlussunnah Wal Jamaah. Learning the Qur'an through the tartila method is a way of learning the Qur'an through the letter function or sound-based approach, namely by learning to read the Arabic letters directly on the sykal. As well as using the production method from reading letters to words, from sentences to reading verses. And the goal is to produce students who have the ability to recite the Qur'an well and recite tajwid. that learning the Qur'an using the tartila method effectively improves the quality of students' reading of the Qur'an in TPQ al-Mubarok.